Three-Dimensional Reconstruction of Friction Stir Welding Microstructure via Serial Sectioning - Said, Nurfatin (Universiti Teknologi Petronas, 2011)
Three-Dimensional Reconstruction of Microstructures is one of the tools to reveal the patterns, shape, area that affected by processing condition. The objectives of this project are to perform serial sectioning as one of the technique of threedimensional microscopy to generate three-dimensional microstructure image and to characterize the effect of friction stir welding on silicon carbide aluminum reinforced microstructure Friction stir welding (FSW) has been successfully used to join aluminum matrix composites in a solid state joining process. The study of the microstructure of the weld joint typically involved common metallography preparation techniques, culminating in two-dimensional micrographs depicting the microstructure of the weld joint. The techniques of serial sectioning and threedimensional reconstruction were employed to characterize the microstructure of silicon carbide (SiC) reinforced aluminum composite joined via the FSW process. Serial sectioning tasks were performed using conventional metallography techniques and equipment; however micrographs of the composite were recorded after each successive polishing step. Using the open source software NIH ImageJ, these micrographs were digitally enhanced and stacked to generate a 3D volume of the composite. The 3D reconstructions showed that a portion of the initial SiC particles were broken up by the FSW process and redistributed in the weld zone. Furthermore, the FSW process appeared to cause some of the unbroken SiC particles to align lengthwise in the welding direction. These characteristics would definitely influence the mechanical behaviour of the weld joint and future work will include the effects of welding parameters on the size and distribution of the SiC particles within the weld zone.